Effect of The Type Impermeable Storage Container on The Quality of Rice Seeds - Hairu Suparto; Riza Adrianoor Saputra; Novitriani Saragih (Gontor AGROTECH Science Journal, 2021)
Rice as a food source that provides carbohydrates for the people of Indonesia, especially South Kalimantan, needs to be increased in production so that the community's needs can be met. The quality of seeds will determine the productivity and quality of seeds. Storage treatment is one way that can be done to maintain seeds until the seeds are planted, but storage treatment that is too long will cause seed deterioration or seed viability to decrease. The decline in seed quality caused by keeping in open spaces storage causes fluctuations in temperature and humidity due to direct interaction with the environment. Efforts to control factors that can affect the rate of seed deterioration can be executed, among others, by using an impermeable storage container. Impermeable storage containers do not support the exchange of air from the environment to the inside of the storage container. The purpose of this study was to determine which type of impermeable storage container is best for the quality of rice seeds. The research has been at the Laboratory of Center for Supervision and Certification of Food Crops and Horticulture Seeds, South Kalimantan Province, Banjarbaru City and used a one-factor CRD with w0 (+) (cans), w0 (-) (plastic sack), w1 (glass jars), w2 (plastic jars) and w3 (aluminum foil). The results of the study indicated that the use of impermeable storage containers had a significant effect on moisture content, germination, and maximum growth potential of rice seeds. The use of the best impermeable storage container for the moisture content of rice seeds in the storage period of 45 days after storage (das) was found in the w3 treatment (aluminum foil) of 11.63%, while the parameter of germination in the 15 das was 63.83%, the maximum growth potential in the storage period of 45 and 90 das was found in the w1 treatment (glass jar) of 73.50% and w0 (+) (cans) of 70.69%.